1989
DOI: 10.1016/s0022-5193(89)80055-4
|View full text |Cite
|
Sign up to set email alerts
|

Idiotypic networks incorporating T-B cell co-operation. The conditions for percolation

Abstract: Previous work was concerned with symmetric immune networks of idiotypic interactions amongst B cell clones. The behaviour of these networks was contrary to expectations. This was caused by an extensive percolation of idiotypic signals. Idiotypic activation was thus expected to affect almost all (> 107) B cell clones. We here analyse whether the incorporation of helper T cells (Th) into these B cell models could cause a reduction in the percolation. Empirical work on idiotypic interactions between Th and B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Thus, in T cell-dependent B cell responses, other cell surface receptors need to be engaged to generate a response, and the degree of their engagement may modulate the response to cross-linking (cf. De Boer and Hogeweg, 1989;Carter and Fearon, 1992; Neumann and Perelson, manuscript in preparation). This means that responses may differ in their requirement for cross-linking, a phenomenon seen in histamine release from human basophils (cf.…”
Section: Cellular Responsementioning
confidence: 99%
“…Thus, in T cell-dependent B cell responses, other cell surface receptors need to be engaged to generate a response, and the degree of their engagement may modulate the response to cross-linking (cf. De Boer and Hogeweg, 1989;Carter and Fearon, 1992; Neumann and Perelson, manuscript in preparation). This means that responses may differ in their requirement for cross-linking, a phenomenon seen in histamine release from human basophils (cf.…”
Section: Cellular Responsementioning
confidence: 99%
“…Other models that have considered the interaction between different antigen-specific cells for the most part have focused on idiotype-antiidiotype networks (30)(31)(32). In this paper, we develop models that combine the dynamics of antigen-specific stimulation and interaction between different lineages (see refs.…”
mentioning
confidence: 99%
“…DeBoer and Hogeweg concluded that idiotype-anti-idiotype network models based on proliferation of antibody production due to antigen stimulation were unable to explain basic immunological phenomena such as regulation, immunity (memory), and self-non-self discrimination making them poor candidates to explain autoimmunity [95]. Whether the inability to successfully model the immune system using idiotype-anti-idiotype network approaches is a mathematical problem or an intrinsic failure of Jerne’s network theory to describe immune system behavior remains to be determined.…”
Section: 4 Theoriesmentioning
confidence: 99%
“…Whether the inability to successfully model the immune system using idiotype-anti-idiotype network approaches is a mathematical problem or an intrinsic failure of Jerne’s network theory to describe immune system behavior remains to be determined. In contrast, Sulzer and Weisbuch [96] developed a differential equation-based model of an immune system regulated by idiotype-anti-idiotype interactions that resolves many of the intrinsic problems that DeBoer and Hogeweg [95] had attributed to network models. Sulzer and Weisbuch found that in the instance where one or both of the idiotype anti-idiotype clones are self-reactive, the system could take on any of three states [96].…”
Section: 4 Theoriesmentioning
confidence: 99%
See 1 more Smart Citation